Peningkatan Membaca Permulaan Melalui Media Flash Card Pada Peserta Didik Kelas 1 UPTD SDN 1 Juntinyuat - Yayang Furi Furnamasari; Aulia Nur Jannah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to improve the beginning reading of low grade students. This research is a research that uses a qualitative descriptive method. Qualitative descriptive is an attempt to explain facts, data or objects qualitatively in the form of language or discourse by interpreting them appropriately and systematically. Data collection techniques used were interviews, observation, demonstration tests. The data that has been collected will then be analyzed using descriptive techniques. The results show that flash card media can improve the beginning reading skills of low grade students which can be seen from the scores before the action. Then it increases when the teacher uses flash card media to students.